Securing Financial Transactions: A Taxonomical Review of Cybersecurity Strategies in Banking - Pallavi Mane; Shrawan Kumar Sharma (Business, Management and Economics: Research Progress Vol. 7, 2024)
The financial sector has become one of the most heavily targeted industries for cyberattacks due to its vast repository of sensitive information and its pivotal role in the global economy. As banking institutions rapidly adopt digital technologies to enhance service delivery and customer experience, they are increasingly exposed to sophisticated cyber threats. This paper presents an extensive taxonomical review of the various cybersecurity strategies employed in the banking sector to secure financial transactions and protect against data breaches, financial fraud, and identity theft. The study categorizes existing cybersecurity mechanisms into distinct classes based on their core functionalities, technological frameworks, and applicability in different contexts of banking operations. The taxonomy is divided into preventive, detective, and corrective strategies, each covering a diverse set of techniques and tools. Preventive measures include encryption standards, secure coding practices, and robust authentication methods such as multi-factor authentication (MFA) and biometric verification. Detective strategies focus on real-time monitoring systems like intrusion detection systems (IDS), artificial intelligence (AI)-driven threat detection, and Security Information and Event Management (SIEM) solutions. Corrective strategies encompass incident response frameworks, disaster recovery plans, and data loss prevention (DLP) measures designed to mitigate damage in the aftermath of a cyberattack. One of the key contributions of this review is an in-depth evaluation of emerging technologies and their role in transforming banking cybersecurity. These include blockchain-based transaction validation, quantum cryptography, AI and machine learning algorithms for anomaly detection, and zero-trust architectures that enforce strict verification at every layer of the network. The paper discusses how these advanced solutions complement traditional security measures and create a multi-layered defense system capable of addressing the increasingly complex threat landscape. The review highlights the importance of regulatory compliance and international standards, such as the Payment Card Industry Data Security Standard (PCI-DSS), General Data Protection Regulation (GDPR), and ISO/IEC 27001, in shaping cybersecurity strategies within banking institutions. Adherence to these standards not only ensures legal compliance but also provides a foundational framework for implementing effective security controls. Furthermore, the study analyzes the cost-effectiveness of different cybersecurity strategies, considering the financial constraints and resource availability that often influence the adoption of advanced technologies in small and medium-sized banking institutions.